Sidney Sheldon's Angel of the dark - Bagshawe, Tilly (William Morrow, 2012)
"When elderly multimillionaire art dealer, Andrew Jakes, is found brutally murdered in his ransacked Hollywood home, his young wife raped and beaten, and his art and jewels stolen, the motive seems pretty clear. But when the investigation doesn't turn up a single, solid lead, the case is closed and his stunning young widow vanishes. A decade passes before Andrew Jakes' estranged son, Matt Daley, does a little digging of his own, only to find that three nearly identical killings have taken place across the globe in recent years. In all cases an elderly, newly wed millionaire is murdered and his wife assaulted. And in each case the widow is the sole beneficiary of the will, but donates all her new found wealth to children's charities... Soon evidence arises pointing to one woman, dubbed by police as the Angel of Death, moving around the globe changing her identity over the years. Matt and former LA investigator Danny Maguire resurrect the old case, but when the so-called widow resurfaces once again it becomes clear that nothing is what it seems... and time is ticking before the Angel of Death claims her next victim"--